Struggling with Development - Mirza Satria Buana (University of Jember, 2022)
This research examines the concept of a regional wide-ranging autonomy principle that aims to promote local uniqueness and traditions and their impact on the rights and protections of traditional communities and their Traditional Knowledge (TK). Empirical data collected from early to mid-2021 in Barito Kuala District, Indonesia, was used. The results revealed that the local government has no practical autonomy, nor does it protect traditional communities from the negative effects of development projects as all regional Bills must uphold the limited affairs stated in the 2014 Regional Autonomy Act. The sources of this bottleneck are the ambiguities in the Constitution and the loopholes in the 2014 Act. These legal flaws are worsened by elite connections in central and local governments creating a ‘trade-off’, in which the local government must uphold the Unitary State doctrine while the central government remains silent about the corrupt political dynasties in the district. This study advances the existing contemporary understanding of decentralization and development projects that often contradict the law. Keywords: Indonesia decentralization; agricultural traditions; law and development; traditional farmers; national and local elites.